Prospective observational cohort study of patients with weaning failure admitted to a specialist weaning, rehabilitation and home mechanical ventilation centre. Issue 3 (8th March 2016) - Mifsud Bonnici, Denise; Sanctuary, Thomas; Warren, Alex; Murphy, Patrick B; Steier, Joerg; Marino, Philip; Pattani, Hina; Creagh-Brown, Ben C; Hart, Nicholas
Abstract : Objectives: According to National Health Service England (NHSE) specialist respiratory commissioning specification for complex home ventilation, patients with weaning failure should be referred to a specialist centre. However, there are limited data reporting the clinical outcomes from such centres. Setting: Prospective observational cohort study of patients admitted to a UK specialist weaning, rehabilitation and home mechanical ventilation centre between February 2005 and July 2013. Participants: 262 patients admitted with a median age of 64.2 years (IQR 52.6–73.2 years). 59.9% were male. Results: 39.7% of patients had neuromuscular and/or chest wall disease, 21% were postsurgical, 19.5% had chronic obstructive pulmonary disease (COPD), 5.3% had obesity-related respiratory failure and 14.5% had other diagnoses. 64.1% of patients were successfully weaned, with 38.2% weaned fully from ventilation, 24% weaned to nocturnal non-invasive ventilation (NIV), 1.9% weaned to nocturnal NIV with intermittent NIV during the daytime. 21.4% of patients were discharged on long-term tracheostomy ventilation. The obesity-related respiratory failure group were most likely to wean (relative risk (RR) for weaning success=1.48, 95% CI 1.35 to 1.77; p<0.001), but otherwise weaning success rates did not significantly vary by diagnostic group. The median time-to-wean was 19 days (IQR 9–33) and the median duration of stay was 31 days (IQR 16–50), with no difference observed between the groups. Weaning centre mortality was 14.5%, highest in the COPD group (RR=2.15, 95% CI 1.19 to 3.91, p=0.012) and lowest in the neuromuscular and/or chest wall disease group (RR=0.34, 95% CI 0.16 to 0.75, p=0.007). Of all patients discharged alive, survival was 71.7% at 6 months and 61.8% at 12 months postdischarge. Conclusions: Following NHSE guidance, patients with weaning delay and failure should be considered for transfer to a specialist centre where available, which can demonstrate favourable short-term and long-term clinical outcomes.